Biomass production and chemical composition of lippia alba (Mill.) N.E.Br. ex britt & wilson in leaves on different plant parts in different seasons - Castro, D. M. [UNESP]; Ming, L. C. [UNESP]; Marques, M. O.M. (International Society for Horticultural Science (ISHS), 2002)
Lippia alba, family Verbenaceae, is widely spread in Central and South American. It's a shurb with a quadrangular branch reaching 1,7m tall. The leaves are membranaceous, petiolate, pubescent with a strong flavor. It's limbs have variable forms with pointed apex, cuneiform or decumbent base, and serrated or crenated bordes. It was determined the best harvest season to biomass production, essential oil content and chemical composition, on different plant parts (apical, medium, basal). It has been observed that, both apical and medium parts represented around 80% of the fresh leaf mass. The foliar biomass yields are about 5 ton/ha in four harvests during an year. The average yield of essential oil considering the three plant parts were 0.15%, 0.47%, 0.46%, 0.55% and 0.61% for summer/98, autumn/98, winter/98, spring/98 and summer/99, respectively. Essential oils showed similar chemical composition either in relation to seasonality, neral, geranial and tcariofilene were the majority compounds.
Keywords: Essential oil; Lippia alba; Phytochemistry; Seasonal variation